O tempo, os direitos fundamentais e o diálogo entre o Processo do Trabalho e o Processo Civil à luz do Novo Código - Silva Junior, Leone Pereira da (2016)
This Doctoral Thesis aimed at bringing legal and extra-legal reflections on the complex issue of Time. In these reflections, Human Rights and Fundamentals have been addressed taking into account the assumption that Time also constitutes a fundamental right. Furthermore, it was established an interlocution between the Labour Procedure and the Civil Procedure in view of the new Civil Procedure Code (Law no. 13105 of 16 March 2015), which came into force in the legal system on March 18, 2016, as determined by the Superior Court of Justice. Within the same rationale, the thesis was developed in the light of Theory of Dialogue of Sources created in Germany by the jurist Erik Jayme, professor at the University of Helderberg, and brought to Brazil by the renowned jurist Claudia Lima Marques, from the Federal University of Rio Grande do Sul. Due to its complexity, a number of related topics were developed, so that the explanation would be didactic and would make it easier the comprehension of the main theme. In this Thesis, Articles 1 to 15 of the New Code of Civil Procedure were analyzed, consolidating a true Law of Introduction to the Brazilian Procedural Law. Likewise, some emphasis was given to the study of Procedural Law principles, highlighting the principle of subsidiarity, combining the renowned articles 769 and 889 of the Consolidation of Labor Laws with Article 15 of the New Code of Civil Procedure. In summary, this thesis had the purpose of studying the fundamental rights, the ideas of Time and the dialogue between Labor Procedure and Civil Procedure based on the novel Civil Procedure Code. In conclusion, it must be pointed out that, within this theoretical and factual complexity, the whole society discusses one of the most intriguing issues of today: how time influences the lives of people, the dynamics of modern society and today's proceedings, serving as a tool for application of the substantive law to particular cases in order to solve conflicts of interest